VALUE TRANSFORMATION IN THE MULTICULTURAL ORGANIZATION - Suryaman, Suryaman (Universitas Brawijaya, Indonesia, 2019)
This study mainly aimed at describing how the value transformation (i.e., cultural diversity or multicultural value) in amulticultural public elementaryschool. The idea of this study departs from the preliminary study of culturally diverse students in elementary schools. This study used a qualitative approach with the case study design.The results show that the school was concerned with culturally diverse students, the school policies provided opportunities for the learners to understand diversity in everyday life, the development of teaching materials was by integrating multicultural values and in extra-curricular activities, and the schoolcreated a conducive climate of learning activities in transforming multicultural values to the learners. The results suggested that the findings of this research can be used as input for effective learning in multicultural schools. The multicultural school's characteristics require some special attention because the characteristics of heterogeneous learners are highly vulnerable to conflicts. Schools with heterogeneous learners are advised to create a conducive climate for conducting teaching and learning activities, particularly in transferring multicultural values.